THE USE OF GENRE-BASED APPROACH IN TEACHING SPEAKING : A case study at a Junior High School in Bandung Barat Regency - Alawiyah, Tuti (2014)
The study investigated the implementation of Genre-based approach in teaching speaking and the problem encountered by the teacher and also the students in its impelementation in one state Junior high school in Lembang, west Java. This study employed a qualitative research design, implementing characteristic of a case study. The data were obtained through observation, close-ended questionnaires and interview. All the data interpreted to answer all research questions. This study revealed that the teacher has understood about the basic principles and stages in Genre-based approach and implemented it well in his teaching and learning process. He really liked to apply the Genre-based approach because of its systematic procedure/method that help him in the teaching and learning process. In fact, the lack of pronounciation became a big problem to the students in practicing their speaking skill. However, based on the teacher's opinion the lack of students' self confidence become a big issue in encouraging his students to practice their speaking skill. Above of all the use of genre-based approach in the teaching and learning process has been implemented well by the teacher and really helpful in making the condusive teaching and learning in the classroom. The problem encountered in encouraging the students to practice their speaking skill in front of the classroom. Keywords : genre-based approach, teaching speaking, lack of self confidence.